Effects of benzopyrene experimental intoxication and its treatment by star anise on hematological parameters in rats - Saleh, Eman Naji; Iktefa Abdul Hamid Mohammed Saeed; Nedhal ibrahim latef (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2023)
This study aimed to explore the effects of benzopyrene experimental intoxication and its treatment by star anise on hematological parameters in rats. 30 male white Swiss rats (Sprague Dawley), aged 3-4 months and weighing between 170-210 g. The rats were divided into six groups: Control (G1), B[a]P (G2), Star Anise 125 mg/kg bw (G3), Star Anise 120 mg/kg bw + B[a]P (G4), Star Anise 125 mg/kg bw + B[a]P (G5), and Star Anise 130 mg/kg bw + B[a]P (G6). Blood was collected by cardiac puncture at end of experiment by using tubes with EDTA and hematological parameters were estimated by using auto blood analyzer. Erythrogram didn’t showed any significant differences between studied groups, while These results showed that exposure to benzopyrene significantly increased all measured WBC parameters, indicating an inflammatory and immunosuppressive response. The mean values of Mid, Gran, L, and total WBC counts in Benzo group were 3.93 ± 0.97, 12.26 ± 1.08, 10.01 ± 1.07, 25.46 ± 1.29, respectively. The mean values of Mid, Gran, L, and total WBC counts in treatment groups significantly decreased in comparison with Benzo group. They are 1.11 ± 0.01, 4.41 ± 0.52, 5.10 ± 0.92, and 10.27 ± 0.31, respectively. These results indicated that benzopyrene can induce an immune response with leukocytosis and a population increase in the absolute granulocyte and lymphocyte, those treatments can reduce these values, indicating the potential protective effects of them on benzopyrene immune toxicity. In conclusion, these results show that the treatment of rats with benzopyrene caused changes in a number of WBC parameters that reflects an immune inflammatory response and could also reflect immunosuppression without any effects on erythrogram. Such changes were reduced by the treatment with Star anis showing higher efficacy, possibly indicating a role for these medicinal plants as protective agents against benzopyrene-induced immunotoxicity.